Accurate full-scale patient-specific Circle of Willis models including aneurysms: A novel manufacturing approach - Jan Gottfried Minkenberg; Lara Bender; Christiane Franz; Rebecca May; Omid Nikoubashman; Martin Wiesmann; Thorsten Sichtermann (PLoS ONE, 2025)
Background Accurate physical replicas of the Circle of Willis (CoW) are valuable for planning neuroendovascular interventions, validating computational simulations, evaluating medical devices and training physicians. Existing methods often replicate only segments of the CoW or lack geometric precision, which is critical for realistic hemodynamic simulations. Objective We introduce a novel, cost-effective manufacturing approach to create full-scale, patient-specific CoW models using fused deposition modeling (FDM) 3D printing and lost core silicone casting. We aim to evaluate the accuracy and reproducibility of this manufacturing process. Methods A patient-specific 3D model of the CoW with four saccular aneurysms was generated from time-of-flight magnetic resonance angiography (TOF-MRA) data. Three identical models were printed using FDM with acrylonitrile styrene acrylate (ASA) for the vascular structure and butenediol vinyl alcohol co-polymer (BVOH) as a water-soluble support material. The printed models were encased in a clear silicone block and the ASA core was then dissolved using acetone. Computed tomography (CT) scans were used to assess geometric accuracy through cloud-to-mesh distance calculations and centerline analysis. Results The median absolute surface deviation between the replicas and the initial model was approximately 309 µm for the entire CoW, with interquartile ranges (IQR) between 360 µm and 444 µm. The aneurysm surfaces exhibited lower deviations, averaging 90 µm. Centerline analysis showed median absolute deviations in vessel radius ranging from 48 µm to 114 µm across key vascular pathways. Statistical analysis confirmed minimal discrepancies between replicas and the initial model. Each replica costs approximately €100 in materials and requires five days to produce. Conclusion The manufacturing approach produces accurate, reproducible full-scale, patient-specific CoW models, including four aneurysms. This method simplifies the production process, reduces costs and maintains high geometric accuracy, making it suitable for hemodynamic studies, device evaluation, and clinical training.